Tadbir Urus Syariah dalam Industri Takaful di Malaysia: Implikasi Pasca Akta Perkhidmatan Kewangan Islam 2013 = Shariah governance of takaful industry in Malaysia: Implications of post islamic financial services act 2013 - Yusof, M.F.M.; Borhan, J.T.; Romli, N. (Penerbit Universiti Kebangsaan Malaysia, 2016)
Takaful industry was first introduced into Malaysia about 30 years ago when the first takaful operator was established to fulfil the need of the Muslim community to be protected based on the Islamic principles. Takaful operations are regulated and supervised by BNM and various changes have been made to ensure the strengthening and stability of the takaful industry including the shariah governance legislation. The aim of this paper is to analyze the legal provisions of Central Bank of Malaysia Act 2009 and Islamic Financial Services Act 2013 in terms of shariah governance in takaful industry at Malaysia. This study interviewed seven informants comprising officers from the Department of Shariah and Shariah Committee of Takaful Company (SPT), which have involved directly in the shariah governance process of takaful industry. The findings indicate that the legal provisions of Islamic Financial Services Act 2013 have given positive implication for shariah governance of takaful industry since the legal provisions are clear and detailed such as the role of the SAC of BNM and the SC of Takaful Operators.